Fundamentals of investments : - Jordan, Bradford D. (McGraw-Hill/Irwin, 2009)
Fundamentals of Investment, Valuation and Management Canadian Edition was written to: 1. Focus on students as investment managers, giving them information they can act on instead of concentrating on theories and research without the proper context. 2. Offer strong, consistent pedagogy, including a balanced, unified treatment of the main types of financial investments as mirrored in the investment world. 3. Organize topics in a way that makes them easy to apply--whether to a portfolio simulation or to real life--and support these topics with hands-on activities. The approach of this text reflects two central ideas. First, there is a consistent focus on the student as an individual investor or investments manager. Second, a consistent, unified treatment of the four basic types of financial instruments--stocks, bonds, options, and futures--focusing on their characteristics and features, their risks and returns, and the markets in which they trade.